2021
DOI: 10.1002/jmv.27452
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long‐term antibody response in COVID‐19 patients by symptoms grade, gender, age, BMI, and medication

Abstract: The first aim of the study was to analyze the change in antibody titer at 15-day intervals until 60 days postsymptom onset (PSO). The second aim was to analyze the relationship between antibody titer and symptom grade, gender, age, body mass index (BMI), medications, vitamin supplements, and herbal therapies. Blood samples were collected from 43 patients (5 mild, 21 moderate, 17 severe diseases), 18 women (41.9%), and 25 men (58.1%), on 15, 30, 45, and 60 days PSO after COVID-19 infection. The serum antibody t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
2
8
1
Order By: Relevance
“…Contrary to our findings, other researchers did not find that higher BMI influences vaccine serological response [21] , [22] , [23] . Our study and these previous studies did not evaluate vaccine efficacy.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, other researchers did not find that higher BMI influences vaccine serological response [21] , [22] , [23] . Our study and these previous studies did not evaluate vaccine efficacy.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, similar correlations between the anti-SARS-CoV-2 antigens responses has not been done, however anti-S1 responses have been shown to correlate with neutralisation ( 12 , 36 ) indicating the RBD region is the main antigenic target of S1, as observed here. The association between disease severity and lasting anti-SARS-CoV-2 responses post infection is inconsistent, with some studies reporting a correlation with disease severity ( 37 ) and higher responses in severe cases ( 17 , 18 ), and others reporting no differences ( 19 , 20 ). In the present study, we found anti-SARS-CoV-2 responses did not differ according to the self-reported symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…During the acute phase of infection, the level of antibody responses has been reported to be associated with disease severity, where those with more severe disease had greater antibody levels ( 13 , 15 ). Contradictory evidence exists on their persistence, with this association reported by some ( 16 18 ), but not all ( 19 , 20 ) studies to continue post-disease. Additionally, reports on the level of the long-term anti-SARS-CoV-2 responses and associations to clinical outcomes are few, although current studies suggest they have no impact on long-COVID ( 8 , 16 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study did not include any follow-up antibodies. A study from Turkey showed no effect of BMI on antibody titres, but the sample size was small and the follow-up period was only 60 days [ 36 ]. Nevertheless, obesity was a risk factor for COVID-19 infection severity in many studies as shown in a meta-analysis of 42 studies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%